Activation of p38 Mitogen-Activated Protein Kinase In Vivo Selectively Induces Apoptosis of CD8(+) but Not CD4(+) T Cells - Merritt, Chris (American Society for Microbiology, 2000)
CD4(+) and CD8(+) T cells play specific roles during an immune response. Different molecular mechanisms could regulate the proliferation, death, and effector functions of these two subsets of T cells. The p38 mitogen-activated protein (MAP) kinase pathway is induced by cytokines and environmental stress and has been associated with cell death and cytokine expression. Here we report that activation of the p38 MAP kinase pathway in vivo causes a selective loss of CD8(+) T cells due to the induction of apoptosis. In contrast, activation of p38 MAP kinase does not induce CD4(+) T-cell death. The apoptosis of CD8(+) T cells is associated with decreased expression of the antiapoptotic protein Bcl-2. Regulation of the p38 MAP kinase pathway in T cells is therefore essential for the maintenance of CD4/CD8 homeostasis in the peripheral immune system. Unlike cell death, gamma interferon production is regulated by the p38 MAP kinase pathway in both CD4(+) and CD8(+) T cells. Thus, specific aspects of CD4(+) and CD8(+) T-cell function are differentially controlled by the p38 MAP kinase signaling pathway.